Molecular Assays on Cutaneous Swabs as an Effective, Non-Invasive Diagnostic Technique for Cutaneous Leishmaniasis: Results from a Retrospective Study Conducted in Italy - Anna Barbiero; Andrea Aiello; Nunziata Ciccone; Simona Pollini; Francesca Malentacchi; Maria Grazia Colao; Gian Maria Rossolini; Costanza Fiorelli; Daniela Massi; Alberto Antonelli; Sara Cuffari; Trentina Di Muccio; et al. (Tropical Medicine and Infectious Disease)
Background: The case confirmation of CL relies on the direct demonstration of the parasite in clinical specimens from skin tissues. Despite most research efforts focusing on biopsy samples as the preferred diagnostic specimen for the detection of Leishmania spp., the use of non-invasive sampling, such as cutaneous swabs, combined with the use of molecular assays, has shown promising results. Methods: We conducted a retrospective study aimed at comparing the performance of different invasive and non-invasive diagnostic techniques, employed for the diagnosis of CL, in an Italian tertiary care center. Results: We observed 29 cases of CL between 2008 and June 2024. Considering the demonstration of Leishmania spp. on culture, biopsy PCR, histology, or smear microscopy as the reference diagnostic test for CL, molecular assays on cutaneous swabs showed a sensitivity of 100% (95% C.I. 73.5–100). Overall, PCR performed on swab specimens allowed for the detection of three cases that biopsy histology (in two cases) and microscopic examination of cutaneous smear (in three cases) would have failed to identify. Conclusion: Non-invasive swab sampling, combined with molecular analysis, can be a valuable tool for a more accessible and patient-friendly diagnostic approach for CL. Should our preliminary results be confirmed, this test could become the first-line diagnostic tool for CL, reserving biopsy as a second-level test or for cases in which the differential diagnosis includes malignancy or other concerning diseases. Further studies aimed at defining the efficiency of this diagnostic method and providing standardized diagnostic protocols would be needed to provide stronger evidence supporting its recommendation.